2008
DOI: 10.1002/polb.21457
|View full text |Cite
|
Sign up to set email alerts
|

Electrically conductive transparent papers using multiwalled carbon nanotubes

Abstract: We describe a novel class of electrically conductive transparent materials based on multiwalled carbon nanotubes (MWCNTs). Transparent nanocomposites were fabricated by incorporating an aqueous silk fibroin solution into bacterial cellulose membranes. The transparent nanocomposites had a high transmittance in the visible and infrared regions, regardless of the bacterial cellulose fiber content, due to the nanosize effect of the bacterial cellulose nanofibrils. This phenomenon allowed the preparation of a novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 24 publications
1
33
0
2
Order By: Relevance
“…Jung et al have reported 2.1 Â 10 À3 Scm À1 for paper composites of multi-walled carbon nanotubes (MWCNTs). 21 We have produced SWCNT-cellulose composites that have conductivities of 3 Â 10 À2 Scm…”
Section: à6 To 10mentioning
confidence: 99%
“…Jung et al have reported 2.1 Â 10 À3 Scm À1 for paper composites of multi-walled carbon nanotubes (MWCNTs). 21 We have produced SWCNT-cellulose composites that have conductivities of 3 Â 10 À2 Scm…”
Section: à6 To 10mentioning
confidence: 99%
“…Yoon and coworkers [5,6] dipped BC membrane in a surfactant-stabilized 0.05 wt% multiwalled CNT (MWCNT) well-dispersed aqueous solution for 24 h, consequently MWCNTs were found to be inserted in the BC membrane and the electrical conductivity of MWCNT/BC composite membranes with different MWCNTs' surfactants, cationic cetyltrimethylammonium bromide (CTAB) or sodium dodecylbenzenesulfonate (NaDDBS), greatly increased to 1.4!10 -1 and 4.2!10 -1 S/cm, respectively. Jung et al [7] also utilized BC membrane as the template to deposit MWCNTs uniformly, then used silk fibroin as coating material for the MWCNT-incorporated BC membrane, the electrical conductivities of the resulting composite membranes consequently achieved respectively 5.3!10 -3 and 3.6!10 -3 S/cm from CTAB-stabilized 0.03 or 0.05 wt% MWCNT aqueous dispersion (immersion time was unaccounted). Kim et al [8] fabricated electrically conductive composite membrane with a surface resistance of 2.8 k"/sq by immersing BC membrane in a NaDDBS-stabilized 0.01 wt% single-walled CNTs (SWCNTs) aqueous dispersion for 3 h. They also fabricated composite membranes containing similar amount of purified MWCNTs or Ag-doped MWCNTs by immersing BC membranes in CTAB-stabilized 0.03 wt% MWCNTs or Ag-doped MWCNTs aqueous dispersions for 24 h, which resulted in comparable electrical conductivities, 2.5!10 -3 and 3.1!10 -3 S/cm, respectively [9].…”
mentioning
confidence: 99%
“…Carbon nanotubes (CNTs), a type of one-dimensional (1-D) carbon nanomaterials with remarkable electrical conductivity, have been utilized in improving the electrical conductivity of insulating BC membranes for use in electronics such as electrodes [5][6][7][8][9][10]. Yoon and coworkers [5,6] dipped BC membrane in a surfactant-stabilized 0.05 wt% multiwalled CNT (MWCNT) well-dispersed aqueous solution for 24 h, consequently MWCNTs were found to be inserted in the BC membrane and the electrical conductivity of MWCNT/BC composite membranes with different MWCNTs' surfactants, cationic cetyltrimethylammonium bromide (CTAB) or sodium dodecylbenzenesulfonate (NaDDBS), greatly increased to 1.4!10 -1 and 4.2!10 -1 S/cm, respectively.…”
mentioning
confidence: 99%
“…Durante a formação da membrana no meio de cultura é possível inserir diversos materiais no meio de cultura para o desenvolvimento de compósitos à base de CB [1], esta forma de obtenção de compósitos pode ser considerada uma inserção "in situ", pois acontece durante o cultivo de Gluconacetobacter xylinus, que insere materiais na sua rede de fibras através da difusão dos mesmos no meio de cultura, o que leva à formação de estruturas com qualidades adicionais. As adições "in situ" vêm sendo bastante utilizadas na literatura, exemplos como hidroxiapatita [34] e colágeno [35] em regeneração óssea guiada e nanotubos de carbono [36] [37], que possui diversas aplicações tecnológi-cas. Essa possibilidade de inserção de materiais nas fibras de CB, não só através do cultivo, mas também com a membrana in natura, levaram recentemente à uma multiplicação das pesquisas com a CB.…”
Section: Avanços Na Produção Da Celulose Bacterianaunclassified